2015
DOI: 10.1186/s13054-015-0820-1
|View full text |Cite
|
Sign up to set email alerts
|

β1-adrenoceptor stimulation promotes LPS-induced cardiomyocyte apoptosis through activating PKA and enhancing CaMKII and IκBα phosphorylation

Abstract: IntroductionCaspase activation and cardiomyocyte apoptosis have been implicated in lipopolysaccharide (LPS)-induced cardiac contractile dysfunction. We have recently demonstrated that β1-adrenoceptor (AR) activation by endogenous norepinephrine contributes to cardiomyocyte apoptosis in endotoxemic mice. Here, we further investigated the molecular mechanisms for the enhancing effect of β1-AR activation on LPS-induced cardiomyocyte apoptosis.MethodsThe adult mouse ventricular myocytes were exposed to LPS, dobuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 40 publications
(51 reference statements)
2
59
2
Order By: Relevance
“…A recent study reported that activated CAMKII inhibits autophagy through attenuating autophagosome formation. Also, overexpression of active CAMKII leads to cardiomyocyte apoptosis . However, whether this kinase has similar impact on OA chondrocytes have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that activated CAMKII inhibits autophagy through attenuating autophagosome formation. Also, overexpression of active CAMKII leads to cardiomyocyte apoptosis . However, whether this kinase has similar impact on OA chondrocytes have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Also, overexpression of active CAMKII leads to cardiomyocyte apoptosis. 59 However, whether this kinase has similar impact on OA chondrocytes have not been investigated. Our results showed that IL-1β stimulation upregulated the phosphorylation level of CAMKII accompanied by the decrease of autophagy marker LC3-II.…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol in severely burned children reduced heart rate and improved catabolism (29). In animal models, β-agonism was associated with increased lipopolysaccharide-induced myocyte necrosis (30) and β-blockade improved cardiac function (28), but the clinical implications of these experimental findings are unclear. Treatments targeted at alleviating right ventricular afterload and reducing right ventricular strain in ARDS are also appealing (27).…”
Section: Discussionmentioning
confidence: 99%
“…Compounds 56 , 57 , and the non-selective beta adrenergic receptor agonist isoproterenol ( 58 ) 314 increase PGC-1α in brown adipose of naïve mice and in models of obesity in a cAMP- and p62-dependent manner. 315 Interestingly, in models of cardiac dysfunction, beta-1 adrenergic receptor stimulation by dobutamine ( 59 ) 316 increases cell death and inflammation, 317 but its blockade by the beta-1 selective antagonist metoprolol ( 60 ) 318 enhances PGC-1α activation and improves cardiac metabolism and function. 319320 Our laboratory has studied beta-2 adrenergic receptor selective agonists in renal MB.…”
Section: Gpcr Ligandsmentioning
confidence: 99%